Penetapan Kadar Cemaran Logam Kadmium (Cd) dalam Jamu Pegal Linu Sediaan Serbuk Secara ICP-OES - Najla Putri Adelaida; Ruth Elenora Kristanty; Ai Emalia Sukmawati; Siti Nur Aliza Fauziah (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2024)
One aspect of safety that needs attention in traditional medicine is the presence of heavy metal contamination. Heavy metal contamination, specifically cadmium (Cd), can occur in herbal products. The presence of cadmium in herbal medicines is highly dangerous to humans due to its toxic nature, which can cause health problems such as bone fragility and breathlessness. Testing is limited to checking the labeling of the herbal medicine logo and determining the level of cadmium contamination in powdered formulations of herbal medicines using Inductively Coupled Plasma – Optical Emission Spectrometry (ICP-OES). The testing aims to determine whether the samples of powdered herbal medicine for joint pain meet the labeling requirements according to the Decree of the Head of the Indonesian Food and Drug Administration No. HK.00.05.4.2411 of 2004 and comply with the cadmium contamination level requirements according to the Regulation of the Indonesian National Agency of Drug and Food Control No. 29 of 2023. The herbal medicine logo on the samples meets the requirements. The cadmium content in the powdered herbal medicine samples is 0.184 mg/kg, which is below the requirement of 0.3 mg/kg. Therefore, it can be concluded that the samples Meet the Requirements (MS).